Pemanfaatan Ekstrak Gulma Air untuk Meningkatkan Pertumbuhan dan Produksi Mikroalga Spirulina platensis pada Kultur Skala Laboratorium - Christiani Christiani; Hexa Apriliana Hidayah (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
Microalgae Spirulina platensis is good as natural food for fish. It consists of the highest protein, that is 70% of the dry weight. On the other hand, it can be used as alternative of healthy food and herbal medicine. To grow well, microalgae need enough nutrition. Another alternative use of the algae is for organic fertilizer. The fertilizer product can increase the income of the fishers, since it can change the useless into usefull things. In the first year, we produced fertilizer in the laboratory and natural food such as microalgae powder. In this research we used an experimental method with Splitplot Design and 3 replications for each treatment of combination of aquatic weeds by giving different concentration. The research result indicates that population growth of microalgae cells is sigmoid with a peak population at the sixth day after inoculation and Salvinia natans with extract concentration of 900 ppm showed the best production for biomass cell of Spirulina platensis.